2022
DOI: 10.1007/s00018-021-04064-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer circulating tumor cells with mesenchymal features—an unreachable target?

Abstract: Circulating tumor cells (CTCs) mediate dissemination of solid tumors and can be an early sign of disease progression. Moreover, they show a great potential in terms of non-invasive, longitudinal monitoring of cancer patients. CTCs have been extensively studied in breast cancer (BC) and were shown to present a significant phenotypic plasticity connected with initiation of epithelial-mesenchymal transition (EMT). Apart from conferring malignant properties, EMT affects CTCs recovery rate, making a significant por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 193 publications
(432 reference statements)
0
6
0
Order By: Relevance
“…Amplification tubes use the gene G3PDH as an internal reference to test the reach of FAM83A in the tumor cell line described above, PCR. The product is cloned into the T vector and sequenced in the same sequence as the gene of interest [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amplification tubes use the gene G3PDH as an internal reference to test the reach of FAM83A in the tumor cell line described above, PCR. The product is cloned into the T vector and sequenced in the same sequence as the gene of interest [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that the total CTCs and their subtypes had a significant clinical association with the prediction of thyroid cancer prognosis. CTCs in the blood stream can often be identified as epithelial, mesenchymal, or both mixed types according to their surface markers with different immunofluorescence stains (34,35). Studies indicate that EMT marker expression in CTCs in a number of types of cancer, such as gastric cancer, colorectal cancer, non-small cell lung cancer, breast cancer and prostate cancer are relevant to invasion and metastasis (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the orchestration of multiple EMT-associated pathways and EMTassociated TFs by Forkhead box O (FOXO) proteins was also documented (Ma et al, 2018). The links with glycobiology (Pucci et al, 2021), Ca 2+ homeostasis (Jones and Hazlehurst, 2021) and the cytoskeleton (Leggett et al, 2021) were also explored, while the complexity of its interrelationships with CSCs (Roy et al, 2021), p53 (Parfenyev et al, 2021) or H 2 O 2 signaling (Milton and Konrad, 2022), and their consequences on the generation of circulating tumor cells (CTCs) (Topa et al, 2022) or occurrence of a collective invasion process (Nagai et al, 2020) were updated. Finally, as EMT is involved in such a broad range of processes associated with malignant transformation and invasiveness, it has become an increasingly interesting target for the development of new therapeutic strategies (Dudas et al, 2020;Jonckheere et al, 2022).…”
Section: Overview Of Emt Driving Parameters In Cancer An Updatementioning
confidence: 99%